Alternative Substrates and Fertilization Routine Relationships for Bedding Pot Plants: Impatiens wallerana - Thibaud, J. (2012)
This study was carried out searching for alternative substrates to traditional peat based on river waste and Sphagnum and Carex peat from Argentinean peatlands and used to grow Impatiens wallerana bedding plant. The aim of this study was i) to characterize physical and chemical effects from seven growing media on I. wallerana plants grown under different fertilization rates and ii) to describe the physiological mechanisms in plants, involved in the use of such substrates. Particle stability was lower for the six alternative substrates compared to the Canadian peat-base control substrate. However, with a high fertilization dose it is possible to reach non significant differences in plant growth compared to the control substrate. It is suggested, for future research, that nitrogen signalling associated to cytokinin synthesis by roots is involved.